Pengaruh Tingkat Inflasi, Nilai Tukar Rupiah dan Harga Minyak Dunia Terhadap IHSG di BEI (Periode 2019-2021) - Susi Anggraeni (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
ABSTRACTAs a source of finance for the corporate community and a platform for community investment, the capital market plays a crucial role in national development. The Indonesia Stock Exchange is the country's primary stock exchange (IDX). In accordance with Law No. 8 of 1995 of the Republic of Indonesia pertaining to the capital market, the capital market consists of activities related to public offerings, securities trading, public companies related to the issuance of securities, and institutions whose professions are related to securities.This research is a quantitative descriptive analysis using monthly data for the 2019-2021 observation period on the inflation rate, rupiah exchange rate, international oil prices, and the JCI. Several tests, including the data validity test, classical assumption test, and data hypothesis testing using multiple linear regression analysis are performed to obtain the findings, and Eviews financial data processing software is utilized to analyze the data.According to the findings of the t-test on the inflation rate, the inflation rate variable (INF) had a substantial influence on the Composite Stock Price Index (CSPI). The rupiah exchange rate variable (KURS) has a notable impact on the Composite Stock Price Index (CSPI). The world oil price (WTI) also has a substantial impact on the Composite Stock Price Index (CSPI). In addition, the f-test indicates that the Inflation Rate (INF), the Rupiah Exchange Rate (KURS), and the World Oil Price (WTI) all have a substantial influence on the Composite Stock Price Index (CSPI) variable concurrently. Keywords: Inflation Rate, Rupiah Exchange Rate, World Oil Price, Composite Stock Price Index (CSPI).